2010 IEEE Instrumentation &Amp; Measurement Technology Conference Proceedings 2010
DOI: 10.1109/imtc.2010.5488094
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved oxygen PWM control and oxygen uptake rate estimation using Kalman Filter in activated sludge systems

Abstract: The measurement and utilization of the oxygen uptake rate (OUR), or respiration rate, is very important in biological wastewater treatment process. It provides information about the biological activity and can indicate the presence of the toxic elements able to corrupt the system. An alternative to the lack of OUR sensors is to use computer codes as software sensors for the estimation of respirometric activity, based on dissolved oxygen (DO) measurements. In this paper the OUR is estimated using Kalman Filter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Dynamic modelling of the wastewater treatment processes has been the topic of various research [9,[13][14][15][16][17][18][19][20][21][22][23][34][35][36][37], and usually with the aim of incorporating control systems leading to improvements in the performance, or with the purpose of designing (or redesigning) WWTPs [9,36]. In [36,37], mathematical models are developed by applying material and energy balances to a process tank, and similar methods are presented in [34,35] where the aeration tank and settler are modelled in Matlab Simulink.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic modelling of the wastewater treatment processes has been the topic of various research [9,[13][14][15][16][17][18][19][20][21][22][23][34][35][36][37], and usually with the aim of incorporating control systems leading to improvements in the performance, or with the purpose of designing (or redesigning) WWTPs [9,36]. In [36,37], mathematical models are developed by applying material and energy balances to a process tank, and similar methods are presented in [34,35] where the aeration tank and settler are modelled in Matlab Simulink.…”
Section: State-of-the-artmentioning
confidence: 99%
“…1 (ASM1) was published by the IAWQ Task Group on Mathematical Modelling for Design of Biological Wastewater Treatment [7]. Since then, the use of simulations in wastewater technology has increased [9], and dynamic modelling of the ASP has been the topic in various research [13][14][15][16][17][18][19][20][21][22][23]. Since the ASM1 was published, the IWAQ/IWA Task Group has published several other models, that add complexity to the ASP models by including additional dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…To use these air pumps for control purposes, it is necessary to trigger them with a PWM control, as it has been described in [5][6][7]. When the aerator is switched on, it takes some time until the oxygen transfer function reaches K max .…”
Section: A Aeration Systemmentioning
confidence: 99%
“…Also, preliminary simulations carried out with the complete model didn't yield good results; hence, this model was not employed in this work. A less complex model, useful to parameter estimation, can be obtained taking into account only the aeration dynamics (5) and the DO dynamics (3). Assuming that the OUR can be considered constant during the time period under investigation, this model is mathematically approximated by…”
Section: A Proposed Modelmentioning
confidence: 99%
“…Simulation results showed that the soft measurement approach based on neural network can estimate the state variables accurately and can be used in real-time monitoring of biochemical wastewater treatment processes. A nonlinear dynamic soft-sensing multi-model based on PLS was proposed byZhao et al (2010) to solve the problem of multi-variable, non-linear and time-varying uncertainty in wastewater treatment process, through selection of such auxiliary variables easily received as water flow and quality, the dissolved oxygen and oxygen aeration Silva et al (2010). estimated the oxygen updateke rate (OUR) using Kalman Filter as a software sensor and the DO concentration was controlled by aerators of on-off type triggered by pulse wide modulation.…”
mentioning
confidence: 99%